Determinants of Institutional Delivery Among Reproductive-age Women in Lumbini, Nepal - Bohara, Pradeep Kumar; Devkota, Bijaya Mani (ILAM इलम, 2026)
In Nepal, maternal health is still a concern issue and institutional delivery is the most direct and immediate way to decrease maternal and neonatal mortality. Insufficiently, nationwide initiatives signify disparities persevering between the institutions across Lumbini Province, as well as socio-demographic and economic factors are also playing significant roles. Thus, this paper focuses on factors determining institutional delivery in women of reproductive age in the Lumbini Province, based on the 2022 Nepal Demographic and Health Survey (NDHS) data. The data were collected using a stratified two-stage sampling design, with 14,545 women faces-naturalizing age-specific experiences of 15-49, and a logistic regression was employed to identify key determinants associated with institutional delivery. The younger women, first-time mothers, educated women, urban dwellers, and wealthier socio-economic quintiles are more likely to have an institutional birth. Significant disparities are present among castes, other ethnicities, religious minorities, and wealth quintiles, so that further targeting viewpoints can be realized for specific intermediation. The economic status plays a significant role, therefore women from the wealthiest households are significantly more given to accessing delivery services. Findings also show that cultural beliefs, ANC visits, and geographical barriers are significantly dishevelled in the determination of healthcare use. Improving institutional delivery rates will mean consideration by policymakers of the financial inducements, growth and development of the healthcare infrastructure and maternal awareness creation as sensitive assistance for targeted groups. Those in developing strategies to maximize improved maternal health within Nepal benefit extremely from the facts that this study generates.